HUBUNGAN KARAKTERISTIK ANTARA BIAYA PEMBANGUNAN INFRASTRUKTUR DENGAN SKALA PENGEMBANGAN KAWASAN PERUMAHAN DAN IMPLIKASINYA - Afriyanie, Dian
The role of infrastructure in housing and settlement development is very important, since infrastructure is a main requirement for developing a healthy, save harmony, and sustainable settlement. On the other side, infrastructure gives an influence in increasing the land price and value. The rising of land price was one of the most influence factor that caused the difficulty of affordability housing provision in urban. The development of large scale housing in fringe area through KASIBA (Kawasan Siap Bangun-Ready to Build Area) and LISIBA (Lingkungan Siap Bangun-Ready to Build Environment) pattern was considered as one of solution to answer the challenge, along with the assumption that the land price in fringe area is cheaper than the price in urban. But the need of infrastructure cost per serviced allotment and per house in large scale housing is more expensive than small scale housing. This caused by the complexity of infrastructure that needed in large scale housing. Large scale housing needs off-site infrastructure and also amenity of public service which is make the differences to small scale housing. The higher amount of infrastructure cost will caused the rising burden of social overhead cost that will be endured by large scale housing developer, and this will cause the high land price and house price in large scale housing. Based on those facts, this research is aim to identify how far the proportion of infrastructure cost in large scale housing and its implication to the production cost and land price. The information will be used to identify the effectiveness of the KASIBA and LISIBA pattern development as an effort to provide large scale housing in mixed use pattern. To achieve the aim of research, some activities was being conducted, such as identify the characteristic of relationship between the need of infrastructure cost and scale of area, and also its implication to the production cost and land price. To identify the characteristic, the method of power regression was being used, based on the assumption that infrastructure cost will tend to be rise monotone toward the scale of area. The research findings show that infrastructure cost will rise continually toward scale of area. Its implication has a significant influence to the rising of house and land price. This implies the highest land price and house price in large scale housing. So that the development of KASIBA and LISIBA pattern will be no longer effective in order to provide mixed-use pattern housing, since the shift of market segment was move away from low income people as an implication of the high land price and house price in large scale housing. However, incentive is needed to achieve the goal of the development of KASIBA and LISIBA pattern, and also to enable KASIBA and LISIBA as a provider of mixed use housing pattern. The incentive could be a package of subsidy from government for low income people, to increase their affordability to buy house or land in KASIBA and LISIBA